Cutting red tape to manage public health threats: An ethical dilemma of expediting antibiotic drug innovation. (20th June 2019) - Munthe, Christian; Nijsingh, Niels
Abstract: Antibiotic resistance, arising when bacteria develop defences against antibiotics, is creating a public health threat of massive proportions. This raises challenging questions for standard notions in bioethics when suitable policy is to be characterized and justified. We examine the particular proposal of expediting innovation of new antibiotics by cutting various forms of regulatory 'red tape' in the standard system for the clinical introduction of new drugs. We find strong principled reasons in favour of such a lowering of the ethical standards of research and the clinical introduction of new antibiotic formulas. However, this support is undermined by pragmatic challenges owing to expected responses from stakeholders, creating uncertainty about which policies could actually be effectively implemented. We describe an underlying dilemma on how to rationally justify compromises between ideal ethical justification and pragmatic risks that needs to be further addressed in this light. We suggest a solution to this dilemma related to proposals of expediting antibiotic drug innovation.